Response to the Letter to the Editor “Delayed diastolic recovery and more prevalent psychiatric disorders in Takotsubo cardiomyopathy” - Nobre Menezes, Miguel (2016)
© 2016 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. All rights reserved.